Residual effect of udaipur rock phosphate sources and farmyard manure on productivity and nutrient uptake by succeeding maize (Zea mays) after wheat (Triticum aestivum) - RAJPUT, S S; SHAKTAWAT, M S; INTODIA, S K (The Indian Journal of Agricultural Sciences, 2011)
A field experimtnt was conducted during the rainy (kharif seasons of 2000 and 2001 on clay-loam soils of Udaipur to investigate the residual effect of sources of udaipur rock phosphate (1 8,3 1 and 34%), incubation methods (no incubation, incubation with phosphate solubilizing bacteria, incubation with farmyard manure and incubation with farmyard manure + phosphate solubilizing bacteria) and farmyard manure (0 and 10 tonnesha) on productivity and nutrient uptake by succeeding maize (Zea mays L.) after wheat (Triticurn aestivum L. emend. Fiori & Paol.). Improvement in yield attributes, yields (grain, stover and biological), nutrient contents and their uptake by maize was not found owing to residual effect of increased level of P fertilization from 40-60 kgha. Residual effect of udaipur rock phosphate applied to wheat crop proved equally effective to diammonium phosphate in influencing productivity as well as nutrient uptake by maize. The agronomic efficacy of both high grade udaipur rock phosphate 3 1% and 34% was better than low grade 18% udaipur rock phosphate in improving the yield attributes, yields (grain, stover and biological) and total uptake of N and P by grain and stover of maize. However, residual effect of incubation methods failed to influence productivity and nutrient uptake by maize crop. Application of farmyard manure @ 10 tonnesiha also had significant residual effect in improving yield attributes, yields (grain, stover and biological), nutrient content in grain and stover and nutrient uptake by succeeding maize after wheat.